Métis Nation Historical Online Database - Manitoba Metis Federation (2021)
"The Métis Nation Historical Online Database is a web-interfaced database that contains textual information extracted from archival documents relevant to the historical Métis Nation. The website also contains high-resolution digital photography and scans of many of the original documents represented in the database. The Historical Online Database allows users to access Métis related archival information, previously only available at Library and Archives Canada (Ottawa) or on microfilm. Importantly, genealogists and Métis users of this website are able to construct Métis family trees using the documents in the database. Providing Métis users with access to their ancestors' documents facilitates the process of cultural re-connection, identity reclamation, and nation building. The Historical Online Database is also a powerful educational tool for teachers, students, curriculum developers, and the general public." [self-description]